2018
DOI: 10.1016/j.amsu.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Self-inflicted and iatrogenic peripheral intravenous cannula fracture: A case report

Abstract: IntroductionWe present a case of broken peripheral intravenous catheter/cannula (PIVC), a well-known, underreported complication of PIVC placement. The fractured cannula could have resulted in intravascular foreign body retention, which is usually iatrogenic.Presentation of caseIn this case, we conceded that both iatrogenic and self-infliction were culpable. The intoxicated, aggressive patient forcefully removed the inserted cannula after repeated attempts by medical personnel to place it. The same cannula was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
8
1
1
Order By: Relevance
“…Unlike in other reports [ 10 , 12 ], the fragment was not palpable in our case. Uncertainty of its location, coupled with its miniature dimensions that would have made it easier to embolize, made us fear it had embolized proximally in the limb as reported by Bloom et al [ 13 ] or even into the chest with potentially life-threatening outcomes as reported by some authors [ [3] , [4] , [5] , [6] ].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Unlike in other reports [ 10 , 12 ], the fragment was not palpable in our case. Uncertainty of its location, coupled with its miniature dimensions that would have made it easier to embolize, made us fear it had embolized proximally in the limb as reported by Bloom et al [ 13 ] or even into the chest with potentially life-threatening outcomes as reported by some authors [ [3] , [4] , [5] , [6] ].…”
Section: Discussioncontrasting
confidence: 87%
“…Similar to other reports [ 9 , 10 ], repeated insertion of the same cannula, which is again a common practice in this resource-limited setting, might have contributed to material failure. The needle could also have punctured the tubing sometime during the procedure similar to what Glassberg et al [ 11 ] and Dell'Amore et al [ 3 ] suggested.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…[1] Spontaneous fracture and migration of intravenous cannula is a rare but known complication first described by Turner et al in 1954. [2] Quality of materials, repeated attempts of catheterization with the same cannula [3] , uncooperative patients and direct trauma to the IV line while in situ are thought to contribute to the incidence of fractured IV cannula [4] . This risk can be reduced by adhering to guidelines, avoiding repeated attempts with the same cannula, avoiding lower extremity IV placement, minimizing catheter movement, placing the smallest suitable catheter size, and removing the catheter as soon as possible.…”
Section: Discussionmentioning
confidence: 99%